Statins and diabetes mellitus: price of collaboration - Andrey Alexeevich Aleksandrov; Maria Nikolaevna Yadrikhinskaya; Svetlana Semenovna Kukharenko; Olga Alexandrovna Shatskaya (Сахарный диабет)
It is now well established that clinical use of statins for primary and secondary prevention of cardiovascular complications in patientswith diabetes mellitus (DM) increases life expectancy. At the same time, meta-analysis of major randomized trials shows statins to increaseglycemic levels and incidence of diabetic symptoms, especially in patients at risk for developing glycemic disorders. However,comparison of positive and negative effects of statins suggests prevalence of clinically beneficial factors.